Prevalence of Elder Abuse and Neglect in Seniors with Psychiatric Morbidity - Example from Central Moravia, Czech Republic - Jan Luzny; Lubica Jurickova (Tehran University of Medical Sciences, 2012)
Background: Elder abuse and neglect (EAN) comprises emotional, financial, physical, and sexual abuse, neglect by other individuals, and self-neglect. Elder abuse and neglect in seniors with psychiatric morbidity was not monitored in the Czech Republic at all, despite the literature shows mental morbidity as one of the important risk factor for developing elder abuse and neglect. Methods: We designed comparative cross sectional study comprising 305 seniors hospitalized in Mental Hospital Kromeriz in June 2011 - group of 202 seniors hospitalized due to mental disorder in psychogeriatric ward and group of 103 seniors hospitalized due to somatic disorder in internal ward. Content analysis of medical records was done in both groups of seniors, with regards to symptoms of elder abuse. Then, we discussed the topic of elder abuse with 30 nurses of psychogeriatric ward in focus group interview. Results: Between two compared groups of seniors we detected statistically higher prevalence of elder abuse in seniors with psychiatric morbidity (48 cases, 23.8% prevalence of EAN), compared to somatically ill seniors (3 cases, 2.9%). As for nursing staff, 5 from 30 nurses (16.7%) have never heard about symptoms of elder abuse and neglect, 10 from 30 nurses (33.3%) had just a partial knowledge about elder abuse and neglect and its symptoms, the rest of nurses (15 from 30 nurses, 50.0%) had good knowledge about elder abuse and neglect and its symptoms. Conclusion: Elder abuse and neglect seems to be a relevant problem in senior population with mental disorders. Development of educational programs for nursing and medical staff about Elder abuse and neglect (symptoms of EAN, early detection of EAN, knowledge how to report cases of EAN) could improve the situation and help mentally ill seniors to better quality of life.